2015
DOI: 10.1186/s12893-015-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary flap reconstruction of tissue defects after sarcoma surgery enables curative treatment with acceptable functional results: a 7-year review

Abstract: BackgroundSarcomas, a heterogeneous group of tumors, are challenging to treat and require multidisciplinary cooperation and planning. We analyzed the efficacy of flap reconstruction in patients with bone and soft tissue sarcoma.MethodsPatient charts and operative records were retrospectively reviewed from January 2006 through October 2013 to identify sarcoma patient characteristics, postoperative complications, revisions, recurrences, and survival. Pedicled and/or free flap reconstruction was performed in 109 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 32 publications
1
47
2
1
Order By: Relevance
“…Lopez et al [2] found that patients who received combined pedicled + free flaps after sarcoma resection had significantly higher wound complications rates compared to patients who received just one, although systemic complications were distributed equally between all groups.…”
Section: Outcomes and Recurrencementioning
confidence: 99%
See 4 more Smart Citations
“…Lopez et al [2] found that patients who received combined pedicled + free flaps after sarcoma resection had significantly higher wound complications rates compared to patients who received just one, although systemic complications were distributed equally between all groups.…”
Section: Outcomes and Recurrencementioning
confidence: 99%
“…[65] 2011 Outcomes Lopez et al . [2] 2015 Outcomes Table 2. Types of flaps used for lower extremity reconstruction based on region Author Year Regions described Flaps described Cordeiro et al .…”
Section: Thighmentioning
confidence: 99%
See 3 more Smart Citations